Implantation of STAR© accelerated system in extensive “dehesa” merino breed farms - Vicario V.; Arrebola F.A.; Pardo B.; Leal C.; Martín R.A.; Borjas F. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
The aim of this study was to improve lamb yield in Merino breed farms in extensive systems by using the STAR© accelerate lambing system. A model farm with lamb production as principal activity from El Valle de Los Pedroches (38.45ºN; 4.9ºW; Cordoba, Spain) was selected for this purpose. During the 9 year period of the field assay, the reproductive rhythm was gradually intensified. Until the year 2003, a natural mating system without control was carried out. From 2004 to 2007, traditional mating system of three lambings in two years in combination with hormonal management was applied. Finally, from 2008 until the present day, the STAR© lambing system was implemented in addition to hormonal treatment. Breeding was carried out every 73 days. Pregnancy diagnosis was performed by ultrasound 43 days after the mating period. Non-pregnant ewes were relocated directly to the breeding-group and pregnant animals were separated. Melatonin (Melovine®) and vaginal sponges (Sincropart® 30 mg) were used in anoestrus mating (March). The results showed that the benefits of the STAR© accelerated lambing system in a medium herd (n = 380), improve work planning (in advance), which increases the farmer’s quality of life and permits labour for other activities, whilst maintaining high productivity. In addition, perinatal mortality during lambing was reduced as a consequence of shortening the mating period (30 days), and production per ewe was improved (flock averages 1.80 lambs per ewe per year). Lastly, an elimination of seasonality on lamb production was achieved, ensuring incomes when prices in the lamb market are higher.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)